A new fusarielin analogue from Penicillium sp. isolated from the Mediterranean sponge Ircinia oros. Issue 39 (23rd September 2015) - Chen, Huiqin; Aktas, Nihal; Konuklugil, Belma; Mándi, Attila; Daletos, Georgios; Lin, Wenhan; Dai, Haofu; Kurtán, Tibor; Proksch, Peter
Graphical abstract: Abstract: The marine-derived fungus Penicillium sp. (strain IO1) isolated from the Mediterranean sponge Ircinia oros yielded a new fusarielin analogue (1 ) together with the known compounds griseofulvin (4 ) and dechlorogriseofulvin (5 ). The structure of 1 was unambiguously elucidated by comprehensive spectroscopic analysis (1D and 2D NMR, and mass spectrometry) as well as by comparison with the literature, while the absolute configuration of 1 was determined on the basis of TDDFT ECD calculations. A further Penicillium sp. (strain IO2) that was isolated from the same sponge I. oros yielded the known compounds dehydrocurvularin (6 ), curvularin (7 ), and trichodimerol (8 ). Co-cultivation of both Penicillium strains (IO1 and IO2) was found to induce the accumulation of the known norlichexanthone (2 ) and monocerin (3 ) that were not detected in either of the two axenic fungal controls. Compounds 3 and 6 showed pronounced cytotoxicity against the murine lymphoma (L5178Y) cell line with IC50 values of 8.4 and 4.7 μM, respectively.